Birrul Walidain in Political Preferences: Harmonizing Family Values and Employment Law in Indonesia - Ahyani, Hisam; Putra, Haris Maiza; Sofanudin, Aji (El-Usrah: Jurnal Hukum Keluarga, 2024)
This study examines the interaction between political preferences and the concept of birrul walidain (the obligation to respect parents) in Indonesia, highlighting its significant impact on individual behavior and familfy dynamics. Using a qualitative approach and literature review, the research reveals that harmonious parent-child relationships positively correlate with career success and political alignment, while differing political beliefs can create familial conflicts affecting overall well-being. The findings underscore the importance of integrating Birrul Walidain principles into workplace policies to support family responsibilities. Furthermore, the study emphasizes Al-Ghazali's concept of maslahah, advocating for the preservation of religious and familial values alongside personal aspirations. By introducing a novel perspective that connects traditional Islamic values with modern employment law, this research aims to inform legal frameworks and workplace practices. Ultimately, the study concludes that the interplay between political preferences and Birrul Walidain offers valuable insights for enhancing employment law and promoting a society that respects both individual rights and family obligations, calling for further research into specific legal reforms aligned with these principles.